Analysis on Deformation Failure and Structural Mechanical Characteristics of Multistage Loess Slope Supported by Frame Structure with Anchors - Kui-bin Yang; Yan-peng Zhu; Lin-ping Wu; Xin-guo Duan; Duo-bang Shi; Xiao-tao Du (Advances in Civil Engineering)
Frame anchor supporting structure is widely accepted in the loess area, especially in the multistage slopes along the road. However, the development between theory and practice is not synchronous, and there exist experience and uncertainty in the design process to a great extent. In response to this problem, the multistage loess slope supported by frame structure with anchors is taken as the research object, and the model test is carried out with the help of the large-scale geotechnical centrifuge under the condition of using prototype materials as much as possible. Then, according to the test data and phenomena, the structural stress and slope deformation concerned in the project are analyzed. The main differences in stress and deformation between the multistage loess slope supported by frame structure with anchors and other types of slopes are pointed out, and some targeted suggestions are given. The research results show that the frame anchor supporting structure and soil can always maintain coordinated deformation during centrifugal loading, and the failure process has certain toughness characteristics. The stress characteristics of the anchor rod and the sliding deformation range of the slope in the multistage loess slope supported by frame structure with anchors are different from the slope with structural surface and single-stage slope. The length of the anchoring section cannot be completely determined based on the potential sliding surface in the design. It is reasonable to strictly control the end position of the anchoring section from the perspective of changing the position of the potential sliding surface. The results obtained can enrich and improve the stability theory of multistage loess slope and provide guidance for engineering practice.